Respuesta :

There are two ways to do this
Method 1:

Find (f-g)(x) first
(f-g)(x) = f(x) - g(x)
(f-g)(x) = (5x^2+3) - (-2x+4)
(f-g)(x) = 5x^2+3+2x-4
(f-g)(x) = 5x^2+2x-1

Then plug in x = -3
(f-g)(-3) = 5(-3)^2+2(-3)-1
(f-g)(-3) = 5(9)+2(-3)-1
(f-g)(-3) = 45-6-1
(f-g)(-3) = 39-1
(f-g)(-3) = 38

-----------------------------------------

Method 2:

Find f(-3)
f(x) = 5x^2+3
f(-3) = 5(-3)^2+3
f(-3) = 5(9)+3
f(-3) = 45+3
f(-3) = 48

Find g(-3)
g(x) = -2x+4
g(-3) = -2(-3)+4
g(-3) = 6+4
g(-3) = 10

Subtract the two results
(f-g)(-3) = f(-3) - g(-3)
(f-g)(-3) = 48 - 10
(f-g)(-3) = 38

-----------------------------------------

Whichever method you pick, the answer is: 38

ACCESS MORE